Balancing the risks of hydraulic failure and carbon starvation: a twig scale analysis in declining Scots pine. (27th June 2015) - Salmon, Yann; Torres‐Ruiz, José M.; Poyatos, Rafael; Martinez‐Vilalta, Jordi; Meir, Patrick; Cochard, Hervé; Mencuccini, Maurizio
Abstract: Understanding physiological processes involved in drought‐induced mortality is important for predicting the future of forests and for modelling the carbon and water cycles. Recent research has highlighted the variable risks of carbon starvation and hydraulic failure in drought‐exposed trees. However, little is known about the specific responses of leaves and supporting twigs, despite their critical role in balancing carbon acquisition and water loss. Comparing healthy (non‐defoliated) and unhealthy (defoliated) Scots pine at the same site, we measured the physiological variables involved in regulating carbon and water resources. Defoliated trees showed different responses to summer drought compared with non‐defoliated trees. Defoliated trees maintained gas exchange while non‐defoliated trees reduced photosynthesis and transpiration during the drought period. At the branch scale, very few differences were observed in non‐structural carbohydrate concentrations between health classes. However, defoliated trees tended to have lower water potentials and smaller hydraulic safety margins. While non‐defoliated trees showed a typical response to drought for an isohydric species, the physiology appears to be driven in defoliated trees by the need to maintain carbon resources in twigs. These responses put defoliated trees at higher risk of branch hydraulic failure and help explain the interaction between carbon starvation and hydraulic failure in dying trees. Abstract : Understanding the physiological responses of leaves to drought is crucial since they are the site of both photosynthesis and transpiration, and hence play key roles in balancing the risks of carbon starvation and hydraulic failure. Co‐occurring healthy and unhealthy Scots pines showed different responses to summer drought: while healthy trees showed a typical response to drought for an isohydric species, atypical physiology in unhealthy trees appears to be driven by the need to maintain carbohydrate availability in needles and twigs. These responses put unhealthy trees at higher risk of branch hydraulic failure and help to explain the interaction between carbon‐starvation and hydraulic failure in dying trees.